Концептуальная модель взаимодействия задач в распределенных системах контроля за ядерно-радиационными материалами - Буртняк, В.М. (Моделювання та інформаційні технології, 2009)
In the article the conceptual model of co-operation of tasks is resulted in the
distributed systems of control by radiation materials. The use of model facilitates the process of creation of the systems considerably.